Targeting PAR2 Overcomes Gefitinib Resistance in Non-Small-Cell Lung Cancer Cells Through Inhibition of EGFR Transactivation - Jiang, Yuhong; Zhuo, Xin; Fu, Xiujuan; Wu, Yue; Mao, Canquan (Frontiers in Pharmacology, 2021)
Drug resistance can notably restrict clinical applications of gefitinib that is a commonly used EGFR-tyrosine kinase inhibitors (EGFR-TKIs) for non-small cell lung cancer (NSCLC). The attempts in exploring novel drug targets and reversal strategies are still needed, since gefitinib resistance has not been fully addressed. Protease-activated receptor 2 (PAR2), a G protein-coupled receptor, possesses a transactivation with EGFR to initiate a variety of intracellular signal transductions, but there is a lack of investigations on the role of PAR2 in gefitinib resistance. This study established that protease-activated receptor 2 (PAR2), actively participated in NSCLC resistant to gefitinib. PAR2 expression was significantly up-regulated when NSCLC cells or tumour tissues became gefitinib resistance. PAR2 inhibition notably enhanced gefitinib to modulate EGFR transactivation, cell viability, migration and apoptosis in NSCLC PC-9 cells and gefitinib-resistant cells (PC-9-GR), suggesting its reversal effects in gefitinib resistance. Meanwhile, the combination of a PAR2 inhibitor (P2pal-18S) and gefitinib largely blocked ERK phosphorylation and epithelial-mesenchymal transition (EMT) compared to gefitinib alone. Importantly, we probed its underlying mechanism and uncovered that PAR2 blockade sensitized gefitinib and reversed its resistance mainly via β-arrestin-EGFR-ERK signalling axis. These effects of PAR2 inhibition were further confirmed by the in vivo study which showed that P2pal-18S reactivated gefitinib to inhibit tumour growth via restricting ERK activation. Taken together, this study could not only reveal a new mechanism of receptor-mediated transactivation to modulate drug resistance, but also provide a novel drug target and direction for overcoming gefitinib resistance in NSCLC.